Ensino superior privado: a permanência dos estudantes que ingressaram por políticas de Financiamento Estudantil – FIES e Programa Universidade para Todos – PROUNI - Felinto, Jislayne Fidelis (2019)
The research falls within the scope of the State reform that changed the educational structures in the 90s, having, as a starting point, the LDB/96 which flexibilized the private higher education institution alisation, that, together with FIES and PROUNI policies, made possible the expansion process towards the democratisation of access. This phenomenon allowed the entry of students with family income between 1 (one) to 3 (three) minimum wage, in private higher education, which are called economically disadvantaged groups. To this end, we searched to investigate the factors that contributed for the permanence of studentes who entered by FIES and PROUNI social policies in the private higher education, with a view that the socioeconomic conditions can be a fator which does not allow the permanence? For this, we searched to analyse the permanence of rhe FIES and PROUNI policies beneficiaries in a private higher education institution at João Pessoa, aiming to identify the major factors that influenced these student permanence. It’s an exploratory qualitative research that culminated with a descriptive and interpretive analysis technique, searching to evaluate the factors that encouraged the private higher education institution former students permanence at João Pessoa - PB, through the use of the instrument entitled “Permanence Evaluation Scale” (NAKAMURA; CASTELO BRANCO; JEZINE, 2016). The data were analyzed on the theoretical focus of Bourdieu (1998) that presents a dialogue that searches viable answers about social fields understanding, here appreciated as a private higher education institution space, that has got an agreed structure, anda t the same time, is mediator of social reproduction, which tends to assimilate behaviours (Habitus) which reveal the impartiality, in the adoption of a dominant speech (high economical, cultural and social capital agents), which allow to understand the analysis category, permanence, in a relationship between aducation and society. However, from this research analysed data, it is concluded that the permanence factors don’t depend of the assisting actions provide by the government or institution, nor the family help, but of the representative significance (symbolic) that the subject attributes to the title and material significance, as a dual societal role , of worker and student, physical institution structure, among others.